Binaural entrainment of 2000-2040 Hz and 2000-2090 Hz increase Glial Fibrillary Acidic Protein (GFAP) expression of astrocytes in the CA1 rat hippocampus during operant learning conditioning - Zainuri Sabta Nugraha; Soedjono Aswin; . Harijadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Astrocytes of hippocampus contribute in the learning performance. Entrainment of gamma wavescan improve learning performance by improving the neurons to astrocytes communication. Theaim of this study was to evaluate the effect of binaural entrainment of 2000-2040 Hz and 2000-2090 Hz on Glial Fibrillary Acidic Protein (GFAP) expression in astrocytes of the CA1 region ofrat hippocampus during operant learning conditions. Twenty male Wistar rats aged 4-6 weekswith body weight 100-150 g were devided into 4 groups. Group I was given binaural soundsentrainment at 2000-2040 Hz without learning test. Group II was given entrainment as performedin Group I followed by a learning test. Group III was given binaural sounds entrainment at 2000-2090 followed by a learning test. Group IV was not given entrainment nor learning test. Theentrainment was performed for 30 minutes everyday for 12 days and the learning test wasperformed for 10 minutes everyday for 12 days. The GFAP expression was examinedimminohistochemically. Astrocytes processes and astrocytes histoscore were also calculated.The results showed that the number of the GFAP-positive astrocytes in Group I (70.96 ± 4.86),II (69.76±3.07) and III (63.10±5.85) were significantly higher than Control (47.33±1.33)(p<0.05). The number of the processes astrocytes in Group I (47.64 ± 3.87), II (60.66±2.07)and III (54.17±6.38) was significantly higher than Control (30.87±2.69) (p<0.05). Moreover,the number of the processes astrocytes in Group II was significantly higher than Group I (p=0.016).The astrocytes histoscore index in the Group II (115.58±14.13) and III (78.32±22.23) weresignificantly higher than Group I (28.79 ± 9.61) and Control (16.05±1.64) (p<0.05). Inconclusion, the binaural entrainment of 2000-2040 Hz and 2000-2090 Hz increase GFAP expressionof astrocytes in Cornu Ammonus 1 (CA1) region of rat hippocampus during operant learningconditioning.